Investigating The Relationships Between Manager’s Coffee Restaurant Dining Experiences and Customer Satisfaction - Nordin, Norhafizi; Amin, Umme Umaimah; Hasbullah, Siti Aminah; Zainol, Noor Azimin; Ideris, Muhamad Shah Kamal (UUM Press, 2021)
The current study investigates the relationships between various service features influencing customers’ satisfaction in the university food service. A research structure consisting of three variables representing dining experiences, namely food quality, service quality, and price are further investigated. Taking Manager’s Coffee restaurant at Universiti Utara Malaysia as a case, this study aims to determine the relationships between dining experiences and students’ satisfaction based on the university restaurant setting. The study was carried out using a quantitative approach involving 200 university students as respondents. The research findings showed that all three dining experiences variables have significant positive relationships on students’ satisfaction. The findings also pointed to improved services and resources particularly to the Manager’s Coffee restaurant, which will increase the market position, especially in the university food service business.